การบริหารจัดการขยะของ เทศบาลตำบลป่าป้อง อำเภอดอยสะเก็ด จังหวัดเชียงใหม่ - เกียรติศักดิ์ กันทาแปง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This study on solid waste management of Papongsubdistrict municipality, DoiSaket district, Chiang Mai province had the objectives to find out the waste problem situation, the waste management of Papongsubdistrict municipality, DoiSaket district, Chiang Mai province, the waste management participation of people in Papongsubdistrict municipality area. In addition, the author also determined the impact to the environment which was from the waste management in the Papongsubdistrict municipality area and the guideline to solve the solid waste management of the municipality by using questionnaire and interview form to collect data. The study result was summarized as follow. There were 336 questionnaire respondents and most of them were female, 56.3%, their ages were between 31-40 years, 44.9%. Additionally, 51.5% of them were sellers, 50.0% were educated with diploma level, 64.9% were married, 54.8% earned income between 5,000-10,000 Baht and 61.9% of the respondents had 1-3 family members. The study result from the questionnaire revealed that the population did not see the importance of the waste management participation in their community for both community planning and 3-years development planning. In term of waste management duration, presently, people were familiar with it, however, they needed more times for waste collection during the festivals or special markets to reduce the accumulated waste. For the impact to the environment, the management did not affect to people’s health or community environment except the smell from the waste collection in specific area only. From the interview of those who took parts in solid waste management or were interested or had experience in waste management i.e. the municipality Administrators: Mayor, Deputy Mayor and Mayor Secretary, Municipal members, Village’s chief, Community Leader and the private Company who was hired to collect the solid waste in the area, it was found that budgeting was the main problem of the waste management as Papong Municipality was a small local administrative organization so the budget was limited. For the participation of the population, the waste was not separated into groups, for instance, the waste was increasing. Therefore, the author suggested that there should be waste separation in the household. Another problem was that there was not any temporary waste pit in the area so there was a problem of disorder. In term of the participation in community planning and 3-years development planning, the population was not interested in proposing any problem though they could do it. The duration of waste collection was appropriate and for the impact to the environment, there was just bad smell from the waste that people placed before the garbage truck collected it.